Α‐Synuclein as a Target for Metallo‐Anti‐Neurodegenerative Agents. (30th November 2022) - Cao, Kaiming; Zhu, Yang; Hou, Zhuanghao; Liu, Manman; Yang, Yanyan; Hu, Hongze; Dai, Yi; Wang, Yu; Yuan, Siming; Huang, Guangming; Mei, Jiaming; Sadler, Peter J.; et al.
Abstract: The unique thermodynamic and kinetic coordination chemistry of ruthenium allows it to modulate key adverse aggregation and membrane interactions of α‐synuclein (α‐syn) associated with Parkinson's disease. We show that the low‐toxic Ru III complex trans ‐[ImH][RuCl4 (Me2 SO)(Im)] (NAMI‐A) has dual inhibitory effects on both aggregation and membrane interactions of α‐syn with submicromolar affinity, and disassembles pre‐formed fibrils. NAMI‐A abolishes the cytotoxicity of α‐syn towards neuronal cells and mitigates neurodegeneration and motor impairments in a rat model of Parkinson's. Multinuclear NMR and MS analyses show that NAMI‐A binds to residues involved in protein aggregation and membrane binding. NMR studies reveal the key steps in pro‐drug activation and the effect of activated NAMI‐A species on protein folding. Our findings provide a new basis for designing ruthenium complexes which could mitigate α‐syn‐induced Parkinson's pathology differently from organic agents. Abstract : The Ru III complex NAMI‐A is activated by hydrolysis and then reacts with specific amino acids in the abundant brain protein α‐synuclein, preventing and disassembling α‐synuclein fibrils, abolishing toxicity toward neuronal cells, and mitigating neurodegeneration and motor impairments in a model of Parkinson's. Since NAMI‐A has a pharmaceutically‐acceptable profile, it has potential for use in treatment of neurodegenerative conditions.